Causes of and people’s responses to petro-conflict in the Niger Delta region of Nigeria - Frederick, Onwubiko Onyemaechi (2016)
Petro-conflict in the Niger Delta area of Nigeria has caused significant disruption of oil business and loss of lives over five decades. The crises escalated from the struggle between the indigenous and the Nigerian government to control oil exploration. In order to understand the causes and responses of the indigenous Niger Delta people to the Petro-conflict, qualitative research methods based on the narrative method of inquiry were used to collect data from the three actors namely; the indigenous people, the oil and gas companies (OGCs) and Nigerian government representatives. The purpose of this qualitative study was to explore the causes of petro-conflict and responses in the Niger Delta Region of Nigeria. The study is guided by the following research objectives; 1. To investigate the main causes of Petro-conflict in the Niger Delta region. 2. To explore provocative confrontations leading to the use of firearms by the militia group to protect the interest of the indigenous Niger Delta. 3. To examine the effect of oil exploring activities by the oil companies in the Niger Delta region. 4. To identify the strategies used by Nigerian government to restore peace in the Niger Delta region. 5. To investigate the perception of the indigenous Niger Delta people towards establishing a lasting peace in the region. The criteria for data collection were that the informants must have had a minimum of 25 years experience of the Petro-conflict in the area. This strategy was used to ensure that the informants supply sufficient data to describe various crises over a reasonable period. This is necessary to gain more insight on the qualitative data obtained through an in-depth interview conducted at the convenience of 12 informants comprising of 4 each from the three actors. Content analysis was used to extract relevant data corresponding to the experiences of the informants. Crisis Decision Theory postulated by Sweeny’s and Coping Theory by Lazarus and Folkman’s were used to explain the causes and responses of the indigenous Niger Delta people to the Petro-conflict. Nigeria government decision and concern was mainly for the interest of protecting the oil resources and neglected the welfare of the indigenous people. This further stir-up among the indigenous because, oil activities has damaged their agricultural lands and rivers, which is their primary sources of livelihood. Research findings shows that the Petro-conflict was intensified by the unfair decision by government. The militant group comprising of indigenous youth often aggressively confronts military forces, further disrupts, and destroys oil and gas pipeline and oil activities. For oil activities to continue, Nigerian government mobilizes the military forces to guard oil exploration activities in the region. The expectation of the indigenous such as providing job opportunities and alternative sources of livelihood has not been satisfied and the Petro-conflict has affected the entire region. The Petroconflict remains a threat in the Niger Delta area as long as the interest of the government is devoted to the resources rather than the people. Although organizing an interview for data collection was very difficult in the Niger Delta area, the research method was appropriate to explore the causes of the Petro-conflict and the responses of the indigenous people.